PENGARUH SPREAD TINGKAT SUKU BUNGA, NON PERFORMING LOAN, DAN BOPO TERHADAP PROFITABILITAS - Ekadini Badung, Ida I Dewa Ayu; Yadnya, I Putu (E-Jurnal Manajemen; Vol 7 No 11 (2018), 2018)
The purpose of this study is to determine the effect of Spread Rate of Interest Rate, NPL and BOPO on Profitability of Rural Banks in Denpasar period 2014-2016. This research uses non participant observation method with the sample used as many as 19 BPR in Denpasar City. Data analysis technique used multiple linear regression analysis. The results of this study show that partially positive Spread has no significant effect on Return On Assets (ROA) on BPR in Denpasar City 2014-2016. Non Performing Loan (NPL) has a significant negative effect on ROA in BPR in Denpasar City 2014-2016. Operational Costs to Operating Income (BOPO) have a significant negative effect on ROA in BPR in Denpasar City 2014-2016. The implications of this study the higher Spread ratio will increase the ROA of banking companies. While the NPL and BOPO the higher the ratio of these variables, then the ROA of banking companies will decrease, so to improve the ROA of banking companies have to press NPL and utilize existing sources and systems. Keywords: Interest Rate Spread, NPL, BOPO, Profitability.